The Use of Grammarly by Tertiary English Language Learners in Their Online Writing Classes - Galuh Puri; Setiamunadi , Antonina Anggraini (Universitas Nusantara PGRI Kediri, 2023)
In writing English texts, grammatical errors are a problem that is always faced by writers. Not to mention other writing errors such as typos, punctuation, and capitalization can also be done by writers. Therefore, the Grammarly application was created to overcome this problem. This study aims to find out how Grammarly helps tertiary-level students in their online Writing Classes. The participants of this study were 78 students studying in an English Language Education study program. A questionnaire was used as the data collection instrument by adopting and adapting closed-ended questions from Hakiki's research (2021) and adding open-ended questions to find out the respondent's perceptions about the use of Grammarly in their online Writing activities. The findings of this study show the majority of respondents perceived Grammarly as a very helpful writing tool. Grammarly helps them by providing vocabulary and grammar suggestions to avoid language errors in their writing, providing mechanics corrections to help them revise their writing errors, and providing plagiarism checkers for premium users.